Pendidikan sebagai Media Membangun Manusia Religius, Humanis, dan Multikulturalis - Mustapa (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2016)
Education is essentially not only the process transferisasi science. But the important thing is how to create a human civilization that is able to humanize humans. Therefore, through this article, the authors offer ideas how to create education that is not only measured in terms of a mere formality, but education should be measured by the extent to which education will be able to create a harmonious life, without discrimination, without violence and without intimidation to continue to make the concept of monotheism as a foundation, and aspires multicultural awareness as strength